Does aid to the productive sectors cause manufacturing sector growth in Africa? - Alain Ndikumana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
In recent decades, Africa has received a large share of official development assistance compared to other regions of the world. Using AidData for 2000-13, this paper examines the effects of aid to productive sectors on manufacturing growth in Africa. Econometric results show that increased assistance to these sectors is associated with an increase in growth of the manufacturing sector, with complementary effects from allocations to economic services and infrastructures. However, dynamic panel regression results show a positive long-term link between increased official development assistance to productive sectors and growth of the manufacturing sector. These findings make an important contribution to the economic literature where there is controversy over aid effectiveness at the macro level. The findings also have policy implications for allocation of aid between sectors by making rational trade-offs related to their amount and quality, with emphasis on productive sectors where investment has a major impact on growth of the manufacturing industry.
Keywords: B22; C23; F35; P33; 330; aid; allocation; productive sectors; growth; manufacturing